Analysis of Village Financial Management in the Village Revenue and Expenditure Budget (APBDesa) Fiscal Year 2021 - Dody Faraitody Teguh; Astri Dwi Andriani; Lutfiatul Zahra (MultiTech Publisher, 2022)
This research aims to analyze village financial management in the Village APBDes. The method used is a qualitative method. Data collection methods were carried out by means of observation, interviews and documentation. The results of this research show that Sindangasih Village has not fully implemented the principles of village financial management in the APBDesa based on Minister of Home Affairs Regulation Number 20 of 2018. At the planning stage, the APBDesa was said to be not optimal because the APBDesa was set on March 15 2021, so it became an obstacle for budget submission. At the implementation stage, the implementation of infrastructure is not yet effective because there is still a lot of development that has not been realized. At the administration stage, Sindangasih Village uses the siskeudes application. However, there is a lack of professionalism in preparing village finances using the Siskeudes application. At the reporting and accountability stage, the Sindangasih village government does not report the implementation report for the first semester, it only reports the APBDesa report in the final semester, namely on 31 December 2021. Furthermore, the Sindangasih Village Government carries out APBDesa accountability in accordance with Minister of Home Affairs Regulation Number 20 of 2018 concerning accountability reports for the realization of the Village APBD and APBDesa realization report and informed to the public through information media